PENGARUH RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM - Intan Purnama, Sri; Ghozali, Agun (Universitas La Tansa Mashiro, 2023)
Share Price is the share price set by the Indonesia Stock Exchange which is determined through the demand and supply of shares, while the acquisition of the share price is obtained from the closing price of the shares. This study aims to determine the effect of Return on Equity, Net Profit Margin and Earning Per Share on the Share Price of LQ45 companies for the 2017 – 2021 period. This research uses quantitative methods. The population in this study is LQ45 companies listed on the Indonesia Stock Exchange for the period 2017 – 2021. The sampling technique is to use purposive sampling technique, which is based on the criteria that have been determined by the researcher. The number of samples in the study was 20 LQ45 companies. Data collection uses documentation techniques and library studies, secondary data in this study is in the form of the Company's financial statements (annual Report) LQ45 for the 2017-2021 period taken from the official website of the Indonesia Stock Exchange www.idx.co.id. The results of the partial test showed that Return On Equity (X1) had a significant effect on the Company's Share Price LQ45, Net Profit Margin (X2) had a significant effect on the company's Share Price LQ45 and Earnings Per Share (X3) had a significant effect on the Company's Share Price LQ45. The results of the simultaneous test showed that simultaneous Return On Equity, Net Profit Margin and Earnings Per Share had a significant effect on the company's share price of LQ45..